Lupus nephritis: Update on aetiopathogenesis and controversies in classification - Pant, AD (Journal of Pathology of Nepal, 2014)
Systemic Lupus Erythematosus; a chronic autoimmune disease; is characterized by loss of tolerance against its own antigens and leads to production of autoantibodies and causes formation and deposition of immune complexes in different organs. Recent articles have been trying to unravel the mysteries of SLE. Different theories that have been proposed for the aetiopathogenesis of SLE are a)The circulating immune complex theory, b) The direct binding to endogenous renal antigens theory, and c) binding of antibody to antigens that were previously ‘planted’ into the kidney. DOI: http://dx.doi.org/10.3126/jpn.v4i8.11596 Journal of Pathology of Nepal; Vol.4,No. 8 (2014) 672-676